DOES REGIONAL INTEGRATION AFFECT EFFICIENCY AND PRODUCTIVITY GROWTH? EMPIRICAL EVIDENCE FROM SOUTH ASIA. Issue 2 (28th March 2016) - Islam, Amirul; Salim, Ruhul; Bloch, Harry
Abstract : This article examines the impact of intra‐regional trade creation initiatives through the South Asian free trade agreement on various aspects of efficiency and productivity growth in South Asia. Applying both stochastic frontier and data envelopment analyses on panel data, this study finds that most countries in South Asia have suffered from a total factor productivity decline, even after the 2006 implementation of the regional free trade agreement. There are, however, substantial variations in technical inefficiencies and total factor productivity growth among the South Asian countries, suggesting possibilities of productivity improvement for lagging countries through cross‐border resource flows.